2022
DOI: 10.3390/ijerph191811204
|View full text |Cite
|
Sign up to set email alerts
|

How Does Digitalization Affect Haze Pollution? The Mediating Role of Energy Consumption

Abstract: In the context of digital technology innovation, an in-depth investigation into the impact of digitalization on haze pollution is of great significance for scientifically understanding environmental effects of digitalization and building a livable civic environment. From the perspective of energy consumption intensity and structure, this paper theoretically analyzes the direct and indirect effects of digitalization on haze pollution. On this basis, the impact of digitalization on haze pollution for 81 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Spatial effects based on spatial geographic weight matrix and economic matrix have both passed the 1% significance test. According to existing research Hao et al, 2023), the digitalization is beneficial to promote the city green economy development and the neighboring effect is significant, and the results are similar with the environment protection [reducing haze pollution (Wang and Xu, 2022) and carbon emissions (Ke et al, 2022)]. To sum up, digitalization can significantly promote urban greening development, but the spatial spillover effect is inconsistent with the findings in green economy and environment protection cases, the reason behind which may be that the urban greening development is a complex transformation process, much more complex than indicators such as green economic development and environment protection.…”
Section: Discussionmentioning
confidence: 95%
“…Spatial effects based on spatial geographic weight matrix and economic matrix have both passed the 1% significance test. According to existing research Hao et al, 2023), the digitalization is beneficial to promote the city green economy development and the neighboring effect is significant, and the results are similar with the environment protection [reducing haze pollution (Wang and Xu, 2022) and carbon emissions (Ke et al, 2022)]. To sum up, digitalization can significantly promote urban greening development, but the spatial spillover effect is inconsistent with the findings in green economy and environment protection cases, the reason behind which may be that the urban greening development is a complex transformation process, much more complex than indicators such as green economic development and environment protection.…”
Section: Discussionmentioning
confidence: 95%
“…The deep integration of digitalization with public health provides great convenience for residents to obtain health information, prevent diseases, and receive medical services, thus positively impacting public health outcomes. Drawing on the research methodology of Wang and Xu (2022), this study selects the internet penetration rate ( ) to measure the level of digitalization of a country [ 53 ]. Furthermore, this study also includes mobile phone penetration rate ( ) as a proxy variable for internet penetration rate to conduct robustness tests.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The study suggested that the optimization and rationalization of industrial structure, technological progress, and trade opening are effective in reducing haze pollution, with market mechanisms proving more efficacious than governmental interventions. Wang & Xu (2022) studied the impact of digitalization on haze pollution and explored the mediating role of energy consumption. Empirical results showed that digitalization can effectively suppress haze pollution, and this inhibitory effect has significant heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%